A practical guide for medical teachers - Dent, John A.; Harden, Ronald M. (Edinburgh : New York : Churchill Livingstone/Elsevier, 2009)
This Third Edition of the highly-praised Practical Guide for Medical Teachers continues to provide a bridge between theoretical aspects of medical education and the practical delivery of enthusiastic teaching. As in its previous editions it will act as an invaluable aid to clinicians as well as other healthcare teachers in their understanding of contemporary educational principles, providing practical help in the delivery of the variety of teaching situations which characterise present day curricula. Key concepts and tips are presented in a digestible form and in a way which indicates both their immediate relevance and practical implications.--Jacket
1. Curriculum development -- 2. Learning situations -- 3. Educational strategies -- 4. Tools and aids -- 5. Curriculum themes -- 6. Assessment -- 7. Staff and students.
Includes bibliographical references and index.
Keywords: Medical education; Medical students; Medicine